2014
DOI: 10.1063/1.4901094
|View full text |Cite
|
Sign up to set email alerts
|

Enabling low-noise null-point scanning thermal microscopy by the optimization of scanning thermal microscope probe through a rigorous theory of quantitative measurement

Abstract: The application of conventional scanning thermal microscopy (SThM) is severely limited by three major problems: (i) distortion of the measured signal due to heat transfer through the air, (ii) the unknown and variable value of the tip-sample thermal contact resistance, and (iii) perturbation of the sample temperature due to the heat flux through the tip-sample thermal contact. Recently, we proposed null-point scanning thermal microscopy (NP SThM) as a way of overcoming these problems in principle by tracking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…1,17 Accordingly, the need to understand thermal transport on the sub-100 nm scale, which is comparable to the width of the ne electrodes in a transistor, necessitates the development of a temperature-sensing method with a sub-100 nm spatial resolution. 1,[13][14][15][16][18][19][20][21][22][23][24][25][26][27] Further, nanoscale thermometry with a high spatial resolution is paramount for accurate thermal characterizations of nanomaterials (e.g., graphene, carbon nanotubes, or nanowires), which have recently drawn enormous amounts of attention. [11][12][13][14][27][28][29][30][31][32][33][34] Related research has been carried out with micro-Raman spectroscopy, 35 thermoreectance (TR), [36][37][38][39][40] near-eld scanning optical microscopy (NSOM), 41 scanning thermal microscopy (SThM), [12][13][14][18][19][20][21][22][23]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,17 Accordingly, the need to understand thermal transport on the sub-100 nm scale, which is comparable to the width of the ne electrodes in a transistor, necessitates the development of a temperature-sensing method with a sub-100 nm spatial resolution. 1,[13][14][15][16][18][19][20][21][22][23][24][25][26][27] Further, nanoscale thermometry with a high spatial resolution is paramount for accurate thermal characterizations of nanomaterials (e.g., graphene, carbon nanotubes, or nanowires), which have recently drawn enormous amounts of attention. [11][12][13][14][27][28][29][30][31][32][33][34] Related research has been carried out with micro-Raman spectroscopy, 35 thermoreectance (TR), [36][37][38][39][40] near-eld scanning optical microscopy (NSOM), 41 scanning thermal microscopy (SThM), [12][13][14][18][19][20][21][22][23]…”
Section: Introductionmentioning
confidence: 99%
“…To meet the demands of nanoscale thermometry with sub-100 nm resolutions, recent studies focus on scanning probebased thermometries. 1,13,14,[18][19][20][21][22][23][24][25][30][31][32][33][34]41,47 Among these technique, in the case of NSOM which measures temperature in near-eld, 41 the spatial resolution is determined by the size of the probe aperture. Accordingly, it requires a very small aperture as well as a complex optical system for high spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, Hwang et al developed a highly sensitive SThM probe whose performance is significantly improved through a systematic design based on quantitative measurement theory; using this highperformance SThM probe, they demonstrated the functionalities of NP SThM with low noise and high spatial resolution. 13 According to Hwang et al, since the spatial resolution of a SThM probe is affected by the intrinsic parameters determined by the design of a probe as well as the extrinsic factors unrelated to the performance of the probe, it is difficult to simply specify a certain value as the spatial resolution of a SThM probe. However, for the SThM probe newly developed by Hwang et al and used in the study reported here, its spatial resolution had been maximized by optimizing the intrinsic parameters so that it was much higher than the previously reported value ($50 nm).…”
mentioning
confidence: 99%
“…A more detailed description of the principles and experimental procedures involved can be found elsewhere. 12,13 When Kim et al derived Eqs. (2) and (3), they did not consider the effect of heat generated in the probe by light.…”
mentioning
confidence: 99%